ANALISIS PENERAPAN AKUNTANSI BERBASIS AKRUAL DALAM PENYAJIAN LAPORAN KEUANGAN PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH PROVINSI SULAWESI UTARA - Lasabuda, Anastasya A.; Morasa, Jenny; Tirayoh, Victorina Z. (Universitas Sam Ratulangi, 2020)
All government entities using funds from national and regional budgets must prepare financial reports referring to government accounting standards which regulated in government regulation No 71 in 2010 and start begin on 2015. The regional goverment financial reports required to be properly according to applicable regulation. Financial reports regional was a responsibility and performance picture in an accounting periods. The purpose of this study was to analyze the accrual basis implementation of SAP No 71 years 2010 and to know the impact ot the financial statement presentation on BPKAD in North Sulawesi Province. Methods used is descriptive qualitative, through observation, interview, analysis and make inferences. The research results showed the application of the base accrued in BPKAD of North Sulawesi Province in the presentation of the financial statements was in accordance with SAP No 71 years 2010. The impact caused by the accounting system based accrual that this report financial more than easier, quick and integrated, and can tell about information budget expended and can be monitored directly by the management to decision maker.